PENGARUH TIME BUDGET PRESSURE DAN HUMAN CAPITAL TERHADAP REDUCED AUDIT QUALITY ACT DENGAN BUDAYA ETIKA ORGANISASI SEBAGAI VARIABEL MODERATING (Studi Empiris pada KAP di Kota Semarang) - Muchammad Sasa Jayeng Basundoro; Agus Purwanto (Diponegoro Journal of Accounting, 2017)
This study aimed to analyze the relationship between time budget pressure and human capital on audit quality through ethical culture of the organization and analyze the influence of cultural mediation organization's ethics against indirect relationship between human capital and time budget pressure on reduced audit quality act.This study uses primary data obtained from questionnaires distributed to the KAP in Semarang and Ernst. This study used a sample of 76 respondents using purposive sampling. The data analysis is done by testing data quality, classic assumption test, and hypothesis testing with multiple linear regression model.The results obtained from this study is that audit quality is directly influenced by human capital, time budget pressure, and ethical culture of the organization. While the organization's ethical culture is directly influenced both of time budget pressure and also human capital on reduced audit quality act.